Antimutagenic efficacy of purified anthocyanin From the in vitro culture of teak leaves on b Marrow cells of mice (Funded Work) - GREESHMA MURUKAN; MURUGAN K. (International Journal of Pharma and Bio Sciences, 2018)
Teak, the tropical timber tree displays a wide variety of pharmacological activities for curing many human ailments. In this study, anthocyanin was extracted from the in vitro callus culture of young leaves, followed by its purification, fractionation and evaluation of antimutagenic activity using a bone marrow micronucleus assay on mice. Male mice (20–30 g) were treated for seven days with purified anthocyanin extract of in vitro cultures from teak leaves at a dose of 100, 200, and 400 mg/kg/day orally, prior to exposure to cyclophosphamide (i.p. 50 mg/kg). Significant amount of anthocyanin was obtained through in vitro callus culture with the phytohormone combination of 2,4-D (2,4-Dichlorophenoxyacetic acid), 1mg/L) and KIN (Kinetin, 2 mg/L) in MS (Murashige and Skoog) medium using leaf explant. Anthocyanin extracted from the callus was subjected to purification and fractionation by column chromatography using silica gel and Amberlite XAD as the column pack. The anthocyanin rich fraction obtained from the purification process was subjected to LCMS/MS analysis and it revealed the presence of peonidn-3-O-glucoside, pelargonidin-3-O-rutinoside, petunidin-3-O-arabinoside, malvidin-3,5-O-diglucoside, cyanidin-3-O-glucosyl rutinoside, pelargonidin-3-O-sophoroside, malvidin-3-O-6”aceyl galactoside, 4’-O-methyl delphinidin 3-O-rutinoside, isopeonidin-3-O-glucoside and cyanidin 3-O-(3”,6”-O-dimalonyl glucoside). Non-mutagenic activity was recorded as the % of decreased micronuclei (MN) and amount of chromosomal aberrations in the anthocyanin pre-treated animals as compared to cyclophosphamide group. Further, the present results revealed that a single administration of all different concentrations of anthocyanin had remarkably decreased the micronucleus formation and chromosomal aberrations in the bone marrow cell of mice of the post cyclophosphamide given group. Thus, the anthocyanin of teak leaves was non genotoxic and antimutagenic against cyclophosphamide-induced mutation